Sensorineural Hearing Loss and its Severity in Patients Suffering from Longstanding Aural Suppuration–An Experience at a Tertiary Care Teaching Hospital - Aria Masoom, Abdul Manan Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: CSOM is the leading cause of hearing loss. It has usually a higher mortality rate than other forms of ear infections. Objective: The aim of this study was to find out the frequency of Sensorineural hearing loss and its severity in patients suffering from longstanding aural suppuration. Material and method: This prospective study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from May 2023 to October 2023 after taking approval from the research committee of the institute. A total of 154 individuals of both sexes and different age groups (12-40 years) presented with chronic CSOM were enrolled in this study. A thorough ENT examination was conducted. The pure tone thresholds for both air and bone conduction were measured across the frequency range of 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz. The two types of hearing impairment were Sensorineural Hearing Loss (SNHL) and Conductive Hearing Loss (CHL). A proforma was used to record the data, and descriptive statistics were used to calculate the frequencies of several variables, including age, gender, the type of hearing loss, and the severity of SNHL. The age groups and length of CSOM were taken into consideration while calculating the severity of SNHL. For the analysis, SPSS 15.0 was used. Results: A total of 154 individuals were examined in this study out of which male were 87 (56.4%) and female were 67 67(43.5%). Conductive hearing loss was diagnosed in 97(63%) individuals and Sensorineural hearing loss in 57(37%) individuals. When patients with persistent otorrhea presented, 37% of them had sensorineural hearing loss and 63% had conductive hearing loss. Moderate hearing loss was the most common among individuals with sensorineural hearing loss (18.8%).The detected cases of conductive hearing loss are not included in the severity analysis. The age group most frequently associated, including 40.2% of the individuals with SNHL, was 12–20 years old. According to tests of significance, a substantial proportion of CSOM patients had sensorineural hearing loss (p-value <0.05). The duration of chronic suppurative otitis media did not positively correlate with the degree of sensorineural hearing loss (p value >.05) Conclusion: The current study concluded that both conductive and sensorineural hearing loss is brought on by chronic suppurative otitis media. Until SNHL complicates it, which is usually permanent, CSOM is a curable cause of acquired deafness. Keywords: Sensorineural; Hearing loss; Severity; Longstanding aural suppuration